Salary Disparities in Public Health Occupations: Analysis of Federal Data, 2021‒2022. - Krasna, Heather; Venkataraman, Malvika; Patino, Isabella (American Journal of Public Health, 2024)
Objectives. To assess salary differences between workers within key public health occupations in local or state government and workers in the same occupations in the private sector. Methods. We used the US Department of Labor's Occupational Employment and Wage Survey (OEWS). Referencing previous studies matching Standard Occupational Classification (SOC) codes with health department occupations, we selected 44 SOC codes. We contrasted median salaries in OEWS for workers in each occupation within state or local government with workers in the same occupations outside government. Results. Thirty of 44 occupations paid at least 5% less in government than the private sector, with 10 occupations, primarily in management, computer, and scientific or research occupations paying between 20% and 46.9% less in government. Inspection and compliance roles, technicians, and certain clinicians had disparities of 10% to 19%. Six occupations, primarily in social work or counseling, paid 24% to 38.7% more in government. Conclusions. To develop a sustainable public health workforce, health departments must consider adjusting their salaries if possible, market their strong benefits or public service mission, or use creative recruitment incentives such as student loan repayment programs for hard-to-fill roles. (Am J Public Health. 2024;114(3):329–339. https://doi.org/10.2105/AJPH.2023.307512)